PENGARUH UPAH MINIMUM DAN PERTUMBUHAN EKONOMI PADA PENYERAPAN TENAGA KERJA DI PROVINSI SUMATERA SELATAN - Akbar, Eghika; Primandari, Novegya Ratih; Akbar, Ali (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
The aim of this research is to find out whether the minimum wage and economic growth have an effect on labor absorption in south sumatra province, either partially or simultaneously. The method used is a quantitative method with multiple linear regression analysis tools. Based on the research results, it is clear that the minimum wage on labor absorption in south sumatra province, where the minimum wage (x1) is 0.229, the coefficient is positive. This means that if the minimum wage (x1) increases by 1 percent, then the average labor absorption (y) will increase by 0.229 percent and the economic growth variable (x2) is -1.752. The coefficient is negative, meaning that if economic growth (x2) increases by 1 percent means the average labor absorption (y) will decrease by 1.752 percent, the coefficient of determination (r square) is 0.969. It can be concluded that the magnitude of the contribution/contribution of the influence of minimum wages (x1) and economic growth (x2), together on variations in the increase/decrease in labor absorption (y) is 96.9% while the remaining 3.1% is influenced by variables others that are not researched such as technology, human development index, population and others.